Integrated transcriptomics and metabolomics analyses of the effects of bagging treatment on carotenoid biosynthesis and regulation of Areca catechu L. - Zheng, Xin; Huang, Liyun; Fan, Benyi; Peng, Chunlin; Iqbal, Amjad; Zhang, Yujie; Chen, Hongman; Ye, Jianqiu; Yang, Yaodong (Frontiers in Plant Science, 2024)
Fresh areca nut fruit commonly found in green or dark green hues. Despite its economic significance, there is currently insufficient research on the study of color and luster of areca. In the current study, the bagging of areca nut fruits (with a double-layered black interior and yellow exterior) were conducted 45 days following pollination, with subsequent harvesting at 120 days after pollination. Remarkably, the exocarp exhibited a notable color transformation, shifting from green to a tender yellow after the bagging process. In this study, we systematically examined the variations in exocarp color and found that the chlorophyll and carotenoid contents of bagged areca nut (YP) exocarp were significantly reduced. We integrated transcriptomics and metabolomics to study the effects of bagging on the carotenoid pathway at the molecular level, and 21 differentially expressed metabolites (DEMs) and 1784 differentially expressed genes (DEGs) were screened. Three key genes in the carotenoid biosynthesis pathway as candidate genes for qPCR validation by co-analysis, which suggested their role in the regulation of pathways related to crtB, crtZ and CYP707A. We described that light intensity may appear as a main factor influencing the noted shift from green to yellow and the ensuing reduction in carotenoid content after bagging.